Analysis of The Factors That Influence The Competitive Advantage of SMEs in The City of Bandung - Uce Karna Suganda; Nanang Rohman (Quantitative Economics and Management Studies, 2023)
This study intends to examine how product innovation and market orientation affect competitive advantage. The focus of this study is on SMEs producing textiles in Bandung. The phrasing of the research question is how market orientation and product innovation impact competitive advantage both separately and concurrently. 50 questionnaires were given using the quota sampling technique to SMEs in the textile industry in Bandung for the purpose of this study. Descriptive and verification research methodologies were employed as the research methodology in this study. Multiple linear regression was employed in the data analysis process. The Statistical Package for Social Science (SPSS) version 22.0 is the data analysis program used. The data analysis results demonstrate that the study hypothesis is verifiable. The finding is that market focus and product innovation significantly and favorably affect competitive advantage. Competitive advantage is positively and significantly impacted by market orientation and positively and significantly impacted by product innovation.